How Impulsivity is Related to Intelligence and Academic Achievement - Vigil-colet, Andreu; Morales-vives, Fabia (The Spanish Journal of Psychology, 2005)
This study investigated the relationships between impulsivity, intelligence, and academia failure in a sample of 241 secondary school students who completed Thurstone’s (1938) Primary Mental Abilities (PMA) test and Dickman’s (1990) and Barratt’s (1985) impulsivity questionnaires (DII and BIS-10, respectively). Results show an inverse relationship between impulsivity and intelligence, specific to the scales with higher loadings on crystallized intelligence, and a positive relationship between impulsivity and academic failure. These results indicate that impulsivity is not directly related to intelligence and may act as a moderator variable between individuals’ resources and their achievements.
Keywords: impulsivity; intelligence; academic achievement